Electrospun polyacrylonitrile nanofibers supported alloyed Pd–Pt nanoparticles as recyclable catalysts for hydrogen generation from the hydrolysis of ammonia borane. Issue 114 (3rd November 2015) - Zhang, Zhen; Jiang, Yanzhou; Chi, Maoqiang; Yang, Zezhou; Wang, Ce; Lu, Xiaofeng
Abstract : Electrospun polyacrylonitrile nanofibers supported alloyed Pd–Pt nanoparticles were synthesized as recyclable catalysts for hydrogen generation from the hydrolysis of ammonia borane. Abstract : Herein, we report the fabrication of polyacrylonitrile (PAN) nanofibers supported Pd–Pt alloy nanoparticles (PAN/Pd–Pt) through a simple and reliable approach by combining an electrospinning technique and in situ reduction process. The resulting PAN/Pd–Pt membranes are composed of a well-defined fiber-like structure with uniform sizes. Pd–Pt alloy nanoparticles are well dispersed on the surface of PAN nanofibers and the composition of alloy nanoparticles can be regulated through adjusting the feed molar ratio of Na2 PdCl4 and K2 PtCl4 . The obtained products are characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) measurements. The as-prepared PAN/Pd–Pt composite exhibits a remarkable catalytic performance towards the hydrogen generation from the hydrolysis of ammonia borane (NH3 BH3, AB). By tuning the composition of the alloy nanoparticles of the nanocatalyst, a turnover frequency (TOF) of 51.9 mol H2 min −1 (mol Pd–Pt alloy) −1 was achieved, much higher than Pd and Pt-based nanocatalysts. In addition, the as-prepared PAN/Pd–Pt composite nanofibers show good recycling stability, as the catalyst can be easily separated from the suspension system. The electrospun nanofiber membrane supported noble metal nanoalloy catalysts shows high potential to find applications for the development of hydrogen generation for clean energy.